Advanced Cultural Districts - Francesconi, Alberto. author. aut Link
VIII, 123 p.
Keywords: Advanced Cultural Districts explores the organisational design issues within the cultural heritage sector, with particular focus on the advanced forms of cultural districts for local socio-economic development.